South Africa's foreign policy and the domestic developmental agenda - Sachikonye, Tawanda (Department of Political Studies, 2024)
This thesis seeks to explore to what extent the domestic developmental agenda (DDA) informs the formulation of South African foreign policy with regards to national development priorities. The DDA does not refer to a formally agreed consensus-based national agenda; instead, it is used in this study to denote a tacit collective understanding at the national level that the post-apartheid South African state must promote socioeconomic development. Post-apartheid South Africa's intensive prioritisation of national development as underpinned by the DDA has had a significant impact on not only domestic economic development policies since 1994, but on South Africa's foreign policy and international relations as well; thereby highlighting how the policybased prioritisation of economic development domestically has been transmitted to both foreign policy formulation and external economic strategy approaches (via economic diplomacy and international trade). Noting the constructivist notion that state identity fundamentally shapes state interests and actions, this study examines how South Africa's post-apartheid identity and the values or aspirations relating to economic development have impacted on foreign policy formulation. The urgency and prioritisation of the DDA has compelled South African state elites in both the governing party and national government to prioritise economic development as the overriding national goal across all public policy streams (foreign policy included). The prioritisation of the DDA is also an outcome of the South African state's ideational identification and projection of what the South African government, and scholars have termed the “Democratic Developmental State” identity. In this regard South African governing elites since 1994 have strived to identify themselves as development champions motivated by a consistent aspiration to realise far-reaching national developmental objectives relating to inequality, joblessness, and poverty. This robust state identification process has consequently shaped the South African state's economic and foreign policies, gradually instilling them with developmental tenets. The Democratic Developmental State identity adopted by the post-apartheid South African state (with widespread national support) and informed by the DDA, has undoubtedly ensured the emergence of a development-oriented foreign policy; and in this regard it provides a sturdy “launch pad” for foreign policy implementation with regards to national development priorities. However, even though it is evident that there is a tangible link between the national development agenda and foreign policy formulation, this study finds that the connection between domestic developmental aspirations (as informed by the DDA) and external policy has not resulted in the establishment of an effective and coordinated policy framework that effectually supports a development oriented foreign policy. This is due to intense (ideological) domestic contestations around the economic development policy framework which should inform the DDA.